2020
DOI: 10.1111/echo.14794
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between coronary microvascular dysfunction and left ventricular diastolic function in patients with chest pain and unobstructed coronary arteries

Abstract: Backgroud Diastolic dysfunction (DD) is reported to affect up to 35% of the adult general population. The consequence of progressive DD is heart failure with preserved ejection fraction (HFpEF). Coronary microvascular dysfunction (CMD) has been suggested as one of the pathologic mechanisms leading to HFpEF. We investigated whether there was an association between coronary microvascular function and echocardiographic indices of left ventricular diastolic function at rest in patients with chest pain and unobstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…Previous studies found that patients with coronary flow velocity reserve < 2 appear to have higher E / e ′ ( P = 0.06) ( 33 ). However, a later study found no association between MBF measured by MCE and diastolic function ( 22 ), consistent with our findings. LAD infarct location has been shown to be independently associated with MVO ( 3 ), consistent with the univariate regression results of this study [LAD as a reference, LCA: OR 0.23 (0.09, 0.58), RCA: OR 0.08 (0.03, 0.23)], but failed to be associated with MBF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies found that patients with coronary flow velocity reserve < 2 appear to have higher E / e ′ ( P = 0.06) ( 33 ). However, a later study found no association between MBF measured by MCE and diastolic function ( 22 ), consistent with our findings. LAD infarct location has been shown to be independently associated with MVO ( 3 ), consistent with the univariate regression results of this study [LAD as a reference, LCA: OR 0.23 (0.09, 0.58), RCA: OR 0.08 (0.03, 0.23)], but failed to be associated with MBF.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have confirmed the diagnostic value of MCE quantitative analysis for microvascular dysfunction ( 19 22 ). It has the potential to identify pathologic microvascular patterns ( 23 ).…”
Section: Discussionmentioning
confidence: 91%
“…получили и проанализировали данные MFR, оцененные с помощью магнитно-резонансной томографии, у 163 пациентов с СНсФВ (73 ± 9 лет; 86 [53%] женщин). Значения MFR были значительно ниже у больных с СНсФВ и неблагоприятными сердечно-сосудистыми событиями, чем у пациентов без них (1,93 ± 0,38 против 2,67 ± 0,52; p < 0,001) и являлись предиктором сердечно-сосудистой смерти и госпитализаций по поводу СН [33]. При этом были обнаружены значимые отрицательные корреляции между MFR и глобальной окружной деформацией (r = -0,29; p < 0,001), глобальной продольной деформацией (r = -0,33; p < 0,001), продольной деформацией правого желудочка (r = -0,26; p < 0,001) и уровнями BNP в сыворотке (r = -0,32; p < 0,001) [34].…”
Section: Discussionunclassified
“…In addition, MCE derived MBF reserve and β reserve were highly correlated with CFVR by TTDE in patients with cardiac syndrome X ( 44 ). A recent study also showed that an MBF reserve <2 by MCE classified 37% of patients with chest pain but no obstructive CAD as having CMD ( 60 ). Although there is no consensus regarding the diagnostic criteria, data regarding CMD by MCE is growing as the rapid development of MCE.…”
Section: Basic Principles Of Myocardial Contrast Echocardiography (Mc...mentioning
confidence: 99%